Are antidementia drugs associated with reduced mortality after a hospital emergency admission in the population with dementia aged 65 years and older? - Hapca, Simona (Alzheimers Dement (N Y), 2019)
INTRODUCTION: People with dementia experience poor outcomes after hospital admission, with mortality being particularly high. There is no cure for dementia; antidementia medications have been shown to improve cognition and function, but their effect on mortality in real-world settings is little known. This study examines associations between treatment with antidementia medication and mortality in older people with dementia after an emergency admission. METHODS: The design is a retrospective cohort study of people aged ≥65 years, with a diagnosis of dementia and an emergency hospital admission between 01/01/2010 and 31/12/2016. Two classes of antidementia medication were considered: the acetylcholinesterase inhibitors and memantine. Mortality was examined using a Cox proportional hazards model with time-varying covariates for the prescribing of antidementia medication before or on admission and during one-year follow-up, adjusted for demographics, comorbidity, and community prescribing including anticholinergic burden. Propensity score analysis was examined for treatment selection bias. RESULTS: There were 9142 patients with known dementia included in this study, of which 45.0% (n = 4110) received an antidementia medication before or on admission; 31.3% (n = 2864) were prescribed one of the acetylcholinesterase inhibitors, 8.7% (n = 798) memantine, and 4.9% (n = 448) both. 32.9% (n = 1352) of these patients died in the year after admission, compared to 42.7% (n = 2148) of those with no antidementia medication on admission. The Cox model showed a significant reduction in mortality in patients treated with acetylcholinesterase inhibitors (hazard ratio [HR] = 0.78, 95% CI 0.72–0.85) or memantine (HR = 0.75, 95% CI 0.66–0.86) or both (HR = 0.76, 95% CI 0.68–0.94). Sensitivity analysis by propensity score matching confirmed the associations between antidementia prescribing and reduced mortality. DISCUSSION: Treatment with antidementia medication is associated with a reduction in risk of death in the year after an emergency hospital admission. Further research is required to determine if there is a causal relationship between treatment and mortality, and whether “symptomatic” therapy for dementia does have a disease-modifying effect.